1981
DOI: 10.1017/s0003356100040538
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein concentration in the diet on milk yield, change in body composition and the efficiency of utilization of body tissue for milk production in ewes

Abstract: 1981). Effects of protein concentration in the diet on milk yield, change in body composition and the efciency of utilization of body tissue for milk production in ABSTRACT Twenty-five mature Finnish Landrace x Dorset Horn ewes, each suckling two lambs, were used to measure the effects of dietary concentration of crude protein on food intake, milk yield and changes in body composition during the first 6 weeks of lactation. Diets were complete mixes of milled hay and concentrates, and the amounts of barley and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 15 publications
3
21
1
1
Order By: Relevance
“…The empty carcass weight decreases during late pregnancy, mostly because of loss of adipose tissue lipid (58,59); hence, the decreased body weight of the ewes at day 2 postpartum was not unexpected. Food intake increases after birth, reaching a plateau between 2 and 3 wk postpartum (24,60). Nevertheless, ewes suckling two or more lambs lose ϳ5 kg in body weight, mostly because of loss of fat from adipose tissue during the first 5-6 wk of lactation (22,23,24,60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The empty carcass weight decreases during late pregnancy, mostly because of loss of adipose tissue lipid (58,59); hence, the decreased body weight of the ewes at day 2 postpartum was not unexpected. Food intake increases after birth, reaching a plateau between 2 and 3 wk postpartum (24,60). Nevertheless, ewes suckling two or more lambs lose ϳ5 kg in body weight, mostly because of loss of fat from adipose tissue during the first 5-6 wk of lactation (22,23,24,60).…”
Section: Discussionmentioning
confidence: 99%
“…Food intake increases after birth, reaching a plateau between 2 and 3 wk postpartum (24,60). Nevertheless, ewes suckling two or more lambs lose ϳ5 kg in body weight, mostly because of loss of fat from adipose tissue during the first 5-6 wk of lactation (22,23,24,60). Ewes suckling a single lamb do not appear to lose adipose tissue lipid, whereas ewes suckling three lambs lose an amount of adipose tissue lipid similar to those suckling two lambs (66).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this higher milk production may have been the result of a greater efficiency in the use of body reserves for milk production, due to a higher protein content in the ration (Cowan et al, 1981 ).…”
Section: Discussionmentioning
confidence: 99%
“…The growth performance of triplet lambs was better than that of twin lambs only with EB silage. Cowan et al (1981) observed higher milk yields with fish meal supplements only during weeks 4 to 6 of lactation, but lamb performance was not reported. In the present study, lamb weight at 6 wk was 1.1 kg higher for ewes receiving EB silage or the 21% CP concentrate compared with FB silage or the 15% CP concentrate, respectively.…”
Section: Discussionmentioning
confidence: 81%